2018
DOI: 10.1016/j.ejbas.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of congenital cataract, its diagnosis and therapeutics

Abstract: Congenital cataract is defined as an opacification of the eye lens appearing at birth or shortly thereafter. Congenital cataract is one of the highest significant causes of blindness or optical impairment in the childhood. Cataract, the cloudiness of the lens is the most frequent reason of blindness worldwide, demonstrating nearly half of all causes of loss of sight worldwide. A significant amount of isolated congenital cataract has monogenic roots. It is genetically heterogeneous, and all the modes of Mendeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…As part of the refractive system, its main function is to transmit and focus light onto the retina due to its transparency, shape and accommodative power [ 1 , 2 , 3 ]. Proteins represent up to 60% of the lens mass, mostly as lens crystallins, whose distribution and stability are critical for light transmission [ 4 , 5 ]. Any disturbance in the cell structure will produce diffraction, absorbance or reflection of the light, which will result in diminished vision [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of the refractive system, its main function is to transmit and focus light onto the retina due to its transparency, shape and accommodative power [ 1 , 2 , 3 ]. Proteins represent up to 60% of the lens mass, mostly as lens crystallins, whose distribution and stability are critical for light transmission [ 4 , 5 ]. Any disturbance in the cell structure will produce diffraction, absorbance or reflection of the light, which will result in diminished vision [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, mutations that cause severe damage to the protein will lead to congenital cataract formation, whereas milder variants only will increase the risk factor to become senile cataracts in the old ages. (7,8) A meta-analysis study reported that approximately 2.4 out of 10,000 children in worldwide were born with congenital cataracts with varying degrees and patterns of lens opacity as its clinical manifestations. (9) In another study, the prevalence of children with cataract disease was reported to occur on 1-15/10,000 births.…”
Section: Congenital Cataractmentioning
confidence: 99%
“…Keratoconus a condition that causes increasing corneal protrusion and thinning, resulting in irregular astigmatism and visual impairment [19] Congenital corneal opacity group of diseases associated with loss of transparency in the corneal tissue at birth or during the first 4 weeks of life [20] Corneal dystrophy a spectrum of inherited corneal abnormalities that are usually bilateral, symmetric, and slowly progressing, with no link to environmental or systemic influences [21] Congenital cataract opacification of the crystalline lens appearing at birth or shortly after [22] Dacryocystitis an inflammation in the nasolacrimal sac, typically caused by an obstruction within the nasolacrimal duct and subsequent stagnation of tears in the lacrimal sac [23] uveitis Inflammation of the uvea, which is comprised of the iris, ciliary body, and choroid. however, any part of the eye can be inflamed.…”
Section: Table 1 Operational Definitions Of the Common Eye Diseasesmentioning
confidence: 99%